Cost-effectiveness analysis of eribulin versus dacarbazine in patients with advanced liposarcoma - Miaomiao Zhang; Jinlong Huang; Xiaochun Zheng; Ping Huang; Xiuli Yang (Scientific Reports)
Abstract A subgroup analysis of a randomized study demonstrated that patients with advanced or metastatic liposarcoma treated with eribulin had longer overall survival and progression-free survival compared to those treated with dacarbazine, suggesting eribulin as a therapeutic option for advanced liposarcoma. Therefore, this study aims to evaluate the cost-effectiveness of eribulin versus dacarbazine in the treatment of advanced liposarcoma. We established a 10-year Markov model to compare the cost-effectiveness of eribulin and dacarbazine regimens. Clinical data were sourced from a subgroup analysis of a multicenter, randomized, open-label phase 3 trials. Quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs) were computed. The total cost of the dacarbazine scheme was $10,895.558, with a QALY of 0.533. In contrast, the total cost of the eribulin scheme was $16,961.891, with a QALY of 0.698. The ICER between the eribulin and dacarbazine schemes was $36,736.467, which is below the willingness-to-pay (WTP) threshold in China ($37,877.469). From the perspective of the Chinese healthcare system, eribulin is cost-effective compared to dacarbazine at the WTP threshold.